A blended fiber SiO 2 Aerogel felt and multi-layer composite structure aerogel products

By laminating the blended fiber SiO2 aerogel felt with flexible fiber felt and vapor barrier film, a multi-layer composite structural aerogel products are formed, which solves the problems of poor flexibility and poor thermal insulation performance of existing aerogel insulating products at low temperatures, and achieves high-efficiency low-temperature insulation and good water vapor barrier properties.

CN117552236BActive Publication Date: 2025-04-22CNCEC HUALU NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311513485.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2025-04-22
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

Existing aerogel thermal insulation products have poor flexibility at low temperatures, insufficient insulation performance, high density, and insufficient water vapor barrier performance, making it difficult to meet the needs of low-temperature cooling conditions.

Method used

The blended fiber SiO2 aerogel felt is used to combine the blended fiber needle felt with SiO2 aerogel in situ to prepare aerogel felt with low volume density and extremely low thermal conductivity, and stack it with the flexible fiber felt and vapor barrier film to form a multi-layer composite structural aerogel product.

Benefits of technology

It achieves comprehensive performance with high efficiency insulation performance, good flexibility, low density and excellent water vapor barrier performance at low temperatures. It is suitable for cold insulation conditions from -200℃ to 125℃, significantly improving the low temperature insulation performance and engineering application advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117552236B_ABST
    Figure CN117552236B_ABST
Patent Text Reader

Abstract

The invention discloses a blended fiber SiO 2 Aerogel felt and multi-layer composite structure aerogel products, the blended fiber SiO 2 Aerogel felt is made of blended fiber needle felt and SiO 2 Aerogel is in-situ composite, with a thickness of 8~12mm and a volume density of 130~180kg / m 3 , thermal conductivity ≤0.016W / (K•m) at 25℃, volume water absorption ≤1%. The aerogel product is composited by fiber felt, the aerogel felt and vapor barrier film. Compared with existing cold-keeping materials, it has the advantages of flexibility, low thermal conductivity, moisture resistance, water vapor barrier, no stress corrosion on stainless steel, and excellent performance indicators. It is suitable for cold-keeping and heat-insulating working conditions from ‑200℃ to 125℃, and has strong pertinence to working conditions and advanced performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogels, and in particular to a blended fiber SiO2 aerogel felt and a multi-layer composite structure aerogel product. Background Art

[0002] In order to help achieve my country's dual carbon goals and implement relevant energy-saving and emission-reduction policies, and to achieve more obvious energy-saving and emission-reduction effects in the field of low-temperature insulation, it is necessary to develop a low-temperature insulation material with excellent performance. However, the common cold insulation materials in China currently have relatively high thermal conductivity, large insulation layer thickness, low insulation efficiency, high energy consumption, difficult inspection and maintenance, and limited construction space. It is difficult to meet the needs of energy conservation and emission reduction. Aerogel is the solid material with the lowest known thermal conductivity. If it is developed into a low-temperature insulation material, it will have the advantages of excellent insulation performance, low moisture absorption rate, good mechanical properties, and easy installation. It can not only meet the needs of efficient cold insulation of the device, but also save energy consumption costs and maintenance costs. It is suitable for a variety of cold insulation conditions and has potential economic and social benefits.

[0003] At present, conventional aerogel insulation products on the market are prepared in the form of felt, sheets, plates, etc., with a thermal conductivity of about 0.021W / (Km) at 25°C and a volume density of 200kg / m 3 If it is directly applied to deep cold conditions, it will have shortcomings such as poor low-temperature flexibility, insufficient low-temperature thermal insulation performance, high density, and substandard water vapor barrier performance. Therefore, it is necessary to develop a flexible, low-heat-conductivity, hot vapor barrier, low-temperature thermal insulation material with strong applicability for low-temperature cold preservation conditions.

[0004] CN114248524A discloses a vapor-proof and waterproof layer, a cold-insulating material, and its preparation method and application. The cold-insulating material is a layered structure, which is composed of an aerogel felt layer and a vapor-proof and waterproof layer from bottom to top; the aerogel felt layer is a glass fiber material filled with silica aerogel; in the aerogel felt layer, the silica aerogel: glass fiber material is (3-10):100 by weight; the vapor-proof and waterproof layer is a layered structure, which is composed of a first PET film layer, a pure aluminum foil layer, and a second PET film layer from bottom to top; the thickness of the first PET film layer is 20-40 μm; the thickness of the second PET film layer is 20-40 μm; the thickness of the pure aluminum foil layer is 5-40 μm. The cold-insulating material has the characteristics of low thermal conductivity, strong water penetration resistance, no condensation after long-term use, non-flammability, good tensile and scratch resistance, etc. However, the thermal insulation material in this scheme is glass fiber felt filled with silica aerogel powder, the filling process is relatively complicated, and the aerogel powder and glass fiber felt cannot be stably combined. In actual applications, the powder loss rate and quality loss are serious, and the thermal insulation and mechanical properties cannot be effectively maintained. At the same time, the amount of aerogel in this aerogel felt is relatively small, and the performance advantages of aerogel cannot be fully utilized; and this method requires evenly coating the surface of the aerogel felt layer with white glue adhesive and then using a hot pressing bonding process to bond it to the vapor barrier and waterproof layer. The process is relatively complicated, and the white glue adhesive will introduce solvents to penetrate into the aerogel felt layer, affecting the thermal insulation, combustion and other properties of the material. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a blended fiber SiO2 aerogel felt to solve the problem that the existing aerogel felt has a high low-temperature thermal conductivity and insufficient thermal insulation performance.

[0006] Furthermore, the present invention also provides a multilayer composite structure aerogel product prepared from the above-mentioned blended fiber SiO2 aerogel felt, which solves the problems of poor low-temperature flexibility, insufficient low-temperature insulation performance, high density and substandard water vapor barrier performance of existing aerogel insulation products.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A blended fiber SiO2 aerogel felt, which is in-situ composited by blended fiber needle-punched felt and SiO2 aerogel, has a thickness of 8-12 mm, and a volume density of 130-180 kg / m 3 , thermal conductivity at 25℃ ≤0.016W / (K•m), volume water absorption ≤1%.

[0009] Furthermore, the blended fiber needle felt is made by blending 60% to 75% by weight of alkali-free glass fiber and 25% to 40% by weight of PET fiber, with a thickness of 12 to 15 mm and a volume density of 40 to 60 kg / m 3 .

[0010] Further, the method is prepared by the following steps:

[0011] (1) Preparation of sol: Mix the silicon source, solvent and catalyst in a mass ratio of 1:3-5.5:0.3-0.6, and stir continuously at 55-60°C for 5-6 hours to prepare a sol;

[0012] (2) preparing a blended fiber SiO2 alcohol gel felt: adding an organic base to the sol obtained in step (1) to adjust the pH to 7-9, then adding the blended fiber needle-punched felt to the obtained sol, impregnating and heating the gel to obtain an alcohol gel felt;

[0013] (3) Aging the gel: placing the alcohol gel felt prepared in step (2) into an alcohol solution, and adding an alkaline solution to the alcohol solution to adjust the pH to 8-9, and aging the solution at an aging temperature of 55°C-65°C for 10h-24h;

[0014] (4) Drying the gel: The alcohol gel felt aged in step (3) is dried by supercritical CO2 to obtain a blended fiber SiO2 aerogel felt.

[0015] Furthermore, in step (1), the silicon source is prepared by mixing methyl orthosilicate and methyltrimethoxysilane or ethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:1 to 1.5; the solvent is methanol or ethanol, and the catalyst is a 0.1 to 0.3 mol / L dilute nitric acid aqueous solution.

[0016] Furthermore, the organic base in step (2) is 0.4-0.8 mol / L tetramethylammonium hydroxide alcohol solution, tetraethylammonium hydroxide alcohol solution or trimethylamine alcohol solution.

[0017] Furthermore, in step (3), the alcohol solution is a methanol or ethanol solution; and the alkaline solution is a tetramethylammonium hydroxide alcohol solution, a tetraethylammonium hydroxide alcohol solution or a trimethylamine alcohol solution.

[0018] A multi-layer composite structure aerogel product, which is composed of fiber felt, the above-mentioned aerogel felt and a vapor barrier film from bottom to top, with a natural thickness of 15±2mm and a volume density of 120~150kg / m 3 , the thermal conductivity at 25℃ is 0.0158~0.164 W / (K·m), and the moisture permeability is 4.7*10 -10 ~8.7*10 -10 g / (m 2 ·s·Pa).

[0019] Furthermore, the fiber felt is a flexible basalt fiber felt or a blended fiber felt with a thickness of 3-5 mm and a volume density of 90-120 kg / m 3 .

[0020] Furthermore, the vapor barrier film is an aluminum foil composite film, and the material structure is POE / Al / PET; wherein the POE layer is 80~90μm, the Al layer is 15~25μm, the PET layer is 20~25μm, and the total thickness of the composite film is 120~140μm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The density of the blended fiber SiO2 aerogel felt material of the present invention is relatively low, and the volume density after drying is only 130-180 kg / m 3 . Excellent thermal insulation performance, thermal conductivity at 95℃ ≤0.018W / (K·m), thermal conductivity at 25℃ ≤0.016W / (K·m), thermal conductivity at -75℃ ≤0.014W / (K·m), thermal conductivity at -125℃ ≤0.012W / (K·m), thermal conductivity at -175℃ ≤0.009W / (K·m).

[0023] 2. The aerogel product of the present invention adopts a multi-layer composite structure of flexible fiber felt, blended fiber SiO2 aerogel felt, and vapor barrier film to prepare a low-temperature low thermal conductivity aerogel product, giving full play to the structural and performance advantages of each layer of material, and through complementation and association, it has excellent comprehensive performance that a single component material does not have, and has stronger applicability and pertinence for low-temperature cold-keeping conditions, and more prominent low-temperature thermal insulation performance and engineering application advantages. Compared with existing cold-keeping materials, it has the performance advantages of flexibility, low thermal conductivity, moisture resistance, water vapor barrier, and no stress corrosion on stainless steel, and has excellent performance indicators. It is suitable for cold-keeping and heat-insulating conditions from -200℃ to 125℃, and has strong pertinence to the working conditions and advanced performance.

[0024] 3. The multi-layer composite structure aerogel product of the present invention has its own vapor barrier film to isolate steam and prevent moisture, eliminating the need for special moisture-proof layer construction during the construction process, ensuring the air tightness of the system and improving the construction speed; it has a flexible felt buffer layer that can maintain elasticity at low temperatures, reducing the risk of material cracking and performance failure caused by vibration at low temperatures, and providing long-term protection for the cold insulation of deep-cold pipelines and equipment with a long-term, low maintenance rate. In addition, the multi-layer composite structure aerogel product of the present invention adopts the form of felt roll packaging, which makes it easy to transport and store, has good flexibility, does not require expansion joints to be set during construction, has low loss, and is simple and quick to install. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a process flow chart for preparing a multi-layer composite structure aerogel product of the present invention;

[0026] Figure 2 It is a schematic diagram of the cross-sectional structure of the multi-layer composite aerogel product of the present invention. DETAILED DESCRIPTION

[0027] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.

[0028] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.

[0029] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.

[0030] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.

[0031] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.

[0032] The quantitative tests in the present invention were all repeated three times, and the results were averaged.

[0033] 1. The present invention provides a blended fiber SiO2 aerogel felt, which is in-situ composited by blended fiber needle-punched felt and SiO2 aerogel, with a thickness of 8-12 mm and a volume density of 130-180 kg / m 3 , thermal conductivity at 25℃≤0.016W / (K·m), volume water absorption≤1%, combustion performance not lower than B1(C) level specified in GB 8624, and passed the stainless steel stress corrosion test.

[0034] The blended fiber needle felt is made by blending 60% to 75% by weight of alkali-free glass fiber and 25% to 40% by weight of PET fiber, with a thickness of 12 to 15 mm and a volume density of 40 to 60 kg / m 3 Compared with pure glass fiber felt, the use of blended fiber felt can effectively reduce the thermal conductivity coefficient. It can still maintain flexibility at lower temperatures without obvious cold brittleness. At the same time, the lower bulk density of the blended fiber felt can also in-situ compound more aerogel, and the final material has better insulation performance and flexibility.

[0035] The specific preparation steps are:

[0036] (1) Preparation of sol: The silicon source, solvent and catalyst are uniformly mixed in a mass ratio of 1:3-5.5:0.3-0.6, and stirred continuously at 55-60°C for 5-6 hours to prepare a sol. The silicon source is prepared by mixing methyl orthosilicate and methyltrimethoxysilane or ethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:1-1.5; the solvent is methanol or ethanol, and the catalyst is a 0.1-0.3 mol / L dilute nitric acid aqueous solution.

[0037] (2) Preparation of blended fiber SiO2 alcohol gel felt: Add an organic base to the sol prepared in step (1) to adjust the pH to 7-9, and then quickly immerse the obtained sol and the blended fiber needle-punched felt in the gel by impregnation and heating to obtain an alcohol gel felt. The organic base is 0.4-0.8 mol / L tetramethylammonium hydroxide alcohol solution, tetraethylammonium hydroxide alcohol solution or trimethylamine alcohol solution. The alkalinity of these three organic bases is stronger than that of general inorganic bases such as ammonia water. Therefore, the use of these three bases for catalysis has better gel performance. At the same time, compared with the conventionally used sodium hydroxide solution and ammonia ammonium fluoride solution, the organic base does not introduce metal ions, chloride ions and fluoride ions, which can effectively avoid the corrosion of the material to stainless steel.

[0038] (3) Aging gel: The alcohol gel felt prepared in step (2) is immersed in a methanol or ethanol solution for aging. Tetramethylammonium hydroxide alcohol solution, tetraethylammonium hydroxide alcohol solution or trimethylamine alcohol solution must be added to the methanol or ethanol to adjust the pH to 8-9. The aging temperature is 55-65°C and the aging time is 10-24h.

[0039] (4) Drying gel: The alcohol gel felt after aging in step (3) is dried by supercritical CO2 to obtain a blended fiber SiO2 aerogel felt. The drying process conditions are CO2 flow rate 450~600L / h, drying temperature 50~55℃, drying pressure 14.5~16.5MPa, and drying time 5~8h.

[0040] The aerogel felt prepared by the above scheme has excellent thermal insulation performance, hydrophobicity and flexibility, and is non-corrosive to stainless steel.

[0041] Second, the present invention also provides a low-temperature low thermal conductivity multi-layer composite structure aerogel product, which is composed of fiber felt, the blended fiber SiO2 aerogel felt of the present invention and a vapor barrier film from bottom to top. Its natural thickness is 15±2mm, and its volume density is 120~150kg / m 3 , the thermal conductivity at 25℃ is 0.0158~0.164 W / (K·m), and the moisture permeability is 4.7*10 -10 ~8.7*10 -10 g / (m 2 ·s·Pa).

[0042] The fiber felt is a flexible basalt fiber felt or a blended fiber felt with a thickness of 3-5 mm and a volume density of 90-120 kg / m 3 The blended fiber felt is made by blending 60% to 75% by weight of alkali-free glass fiber and 25% to 40% by weight of PET fiber.

[0043] The vapor barrier film is an aluminum foil composite film with a material structure of POE / Al / PET, wherein the POE (thermoplastic elastomer) layer is 80-90 μm, the Al layer is 15-25 μm, and the PET (polyester film) layer is 20-25 μm. The total thickness of the composite film is 120-140 μm, and the appearance is smooth without bubbles or wrinkles, and the gram weight is ≥170 g / m 2 , transverse and longitudinal tensile strength are ≥30MPa, water vapor transmission rate ≤0.001g / (m 2 h). The present invention adopts a thick customized aluminum foil composite film, which has a low emissivity to thermal radiation energy, so that it has excellent water vapor barrier performance and thermal insulation performance. The POE layer has a low hot melting temperature and good heat sealing performance, and can play a bonding role with the aerogel felt. The PET layer plays a role in protecting the aluminum foil layer and blocking air and water. The overall structure and performance of the composite film are highly suitable for low-temperature insulation systems.

[0044] The multi-layer composite structure aerogel product is made by sewing fiber felt and blended fiber SiO2 aerogel felt with polyester twisted yarn, nylon twisted yarn or aramid twisted yarn to combine the upper and lower layers, and then attaching a layer of vapor barrier film to the outer surface of the sewn aerogel felt through a hot pressing process. Among them, the fiber felt is used as the inner layer, which is in direct contact with the cold-insulated surface during operation. The fiber felt can maintain elasticity at low temperatures, absorb the stress caused by pipeline equipment vibration and external force impact to a certain extent, and act as a buffer layer; the blended fiber SiO2 aerogel felt is used as the middle layer, and its extremely low thermal conductivity can provide excellent thermal insulation for the material as a whole; the vapor barrier film is used as the outer layer of the material as a whole, and it has excellent barrier properties, which can provide the material as a whole with the effect of blocking water vapor penetration, waterproofing and moisture-proofing, and preventing the failure of the cold-insulation system.

[0045] 3. Embodiment

[0046] Example 1

[0047] See also Figure 1 A low-temperature low thermal conductivity multilayer composite structure aerogel product is prepared by the following method, which specifically includes the following steps:

[0048] (1) Preparation of sol: a mixture of methyl orthosilicate and methyltrimethoxysilane in a molar ratio of 1:1 was uniformly mixed with methanol and a 0.1 mol / L dilute nitric acid aqueous solution in a mass ratio of 1:3.5:0.5, and stirred continuously at 58°C for 5 h to prepare a sol;

[0049] (2) Preparation of blended fiber SiO2 alcohol gel felt: 0.4 mol / L tetramethylammonium hydroxide alcohol solution was added to the sol prepared in step (1) to adjust the pH to 8, and then the mixed sol was quickly impregnated with glass fiber / PET blended fiber needle felt and heated to obtain alcohol gel felt, wherein the blended fiber needle felt was 70wt% alkali-free glass fiber + 30wt% PET fiber blended needle felt, with a thickness of 15mm and a volume density of 40kg / m 3 ;

[0050] (3) Aging of blended fiber SiO2 alcohol gel felt: The alcohol gel felt prepared in step (2) was immersed in an alkaline methanol solution for aging. The alkalinity in the methanol was adjusted to pH 8.5 by tetramethylammonium hydroxide alcohol solution. The aging temperature was 60°C and the aging time was 15 h.

[0051] (4) Preparation of blended fiber SiO2 aerogel felt: The alcohol gel felt aged in step (3) was subjected to supercritical CO2 drying to obtain a blended fiber SiO2 aerogel felt, wherein the drying process conditions are CO2 flow rate 500 L / h, drying temperature 55°C, drying pressure 15 MPa, and drying time 5 h;

[0052] (5) Preparation of multi-layer composite aerogel products: The blended fiber SiO2 aerogel felt prepared in step (4) was mixed with a 5 mm thick and 100 kg / m 3 The 70wt% alkali-free glass fiber + 30wt% PET fiber blended needle-punched felt is sewn with 120tex polyester twisted yarn to combine the upper and lower layers, and then a layer of 140μm POE / Al / PET aluminum foil composite film is hot-pressed on the outer surface of the sewn aerogel felt by hot pressing, and finally a multi-layer composite structure aerogel product is obtained. The structure of the obtained multi-layer composite structure aerogel product is as follows Figure 2 shown.

[0053] The blended fiber SiO2 aerogel felt sample prepared above has a volume density of 150kg / m 3According to GB / T 10294-2008, the thermal conductivity is 0.0171W / (K·m) at 95℃, 0.0145W / (K·m) at 25℃, 0.0126W / (K·m) at -75℃, 0.0106W / (K·m) at -125℃ and 0.0074W / (K·m) at -175℃. The thermal conductivity at each temperature point is excellent.

[0054] The above multi-layer composite structure aerogel product has been tested and its natural thickness is 15mm and its volume density is 133kg / m 3 , the thermal conductivity at 25℃ is 0.0158W / (K·m), and the moisture permeability is 5.4*10 -10 g / (m 2 ·s·Pa). The product has good flexibility, good bending, compression and rebound performance, and after being soaked in liquid nitrogen for 72 hours, the material has no cracking or delamination.

[0055] Example 2

[0056] A low-temperature low thermal conductivity multi-layer composite structure aerogel product is prepared by the following method, which specifically includes the following steps:

[0057] (1) Preparation of sol: a mixture of methyl orthosilicate and methyltrimethoxysilane in a molar ratio of 1:1.5, methanol and a 0.15 mol / L dilute nitric acid aqueous solution in a mass ratio of 1:5:0.4 were uniformly mixed, and stirred continuously at 58°C for 6 h to prepare a sol;

[0058] (2) Preparation of blended fiber SiO2 alcohol gel felt: 0.6 mol / L tetramethylammonium hydroxide alcohol solution was added to the sol prepared in step (1) to adjust the pH to 8, and then the mixed sol was quickly impregnated with glass fiber / PET blended fiber needle felt and heated to obtain alcohol gel felt, wherein the blended fiber needle felt was 65wt% alkali-free glass fiber + 35wt% PET fiber blended needle felt, with a thickness of 13mm and a volume density of 60kg / m 3 ;

[0059] (3) Aging of blended fiber SiO2 alcohol gel felt: The alcohol gel felt prepared in step (2) was immersed in an alkaline methanol solution for aging. The alkalinity in the methanol was adjusted to pH 8 by tetramethylammonium hydroxide alcohol solution. The aging temperature was 55°C and the aging time was 10 h.

[0060] (4) Preparation of blended fiber SiO2 aerogel felt: The alcohol gel felt aged in step (3) was subjected to supercritical CO2 drying to obtain a blended fiber SiO2 aerogel felt, wherein the drying process conditions are CO2 flow rate 500 L / h, drying temperature 55°C, drying pressure 15 MPa, and drying time 5 h;

[0061] (5) Preparation of multi-layer composite aerogel products: The blended fiber SiO2 aerogel felt prepared in step (4) was mixed with a 4 mm thick and 115 kg / m 3 The basalt fiber felt is made of 88.5tex aramid twisted yarn through a sewing process to combine the upper and lower layers, and then a layer of 120μm POE / Al / PET aluminum foil composite film is hot-pressed on the outer surface of the sewn aerogel felt through a hot pressing process, and finally a multi-layer composite structure aerogel product is obtained.

[0062] The blended fiber SiO2 aerogel felt sample prepared above has a volume density of 142kg / m 3 According to GB / T 10294-2008, the thermal conductivity is 0.0183W / (K·m) at 95℃, 0.0158W / (K·m) at 25℃, 0.0141W / (K·m) at -75℃, 0.0119W / (K·m) at -125℃ and 0.0092W / (K·m) at -175℃. The thermal conductivity at each temperature point is excellent.

[0063] The above multi-layer composite structure aerogel product has been tested and its natural thickness is 13mm and its volume density is 129kg / m 3 , the thermal conductivity at 25℃ is 0.0164W / (K·m), and the moisture permeability is 8.7*10 -10 g / (m 2 ·s·Pa). The product has good flexibility, good bending, compression and rebound performance, and after being soaked in liquid nitrogen for 72 hours, the material has no cracking or delamination.

[0064] Example 3

[0065] A low-temperature low thermal conductivity multi-layer composite structure aerogel product is prepared by the following method, which specifically includes the following steps:

[0066] (1) Preparation of sol: a mixture of ethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:1 was uniformly mixed with ethanol and a 0.2 mol / L dilute nitric acid aqueous solution in a mass ratio of 1:3:0.5, and stirred continuously at 60°C for 6 h to prepare a sol;

[0067] (2) Preparation of blended fiber SiO2 alcohol gel felt: 0.6 mol / L trimethylamine alcohol solution was added to the sol prepared in step (1) to adjust the pH to 8, and then the mixed sol was quickly impregnated with glass fiber / PET blended fiber needle felt and heated to obtain alcohol gel felt, wherein the blended fiber needle felt was 70wt% alkali-free glass fiber + 30wt% PET fiber blended needle felt, with a thickness of 14mm and a volume density of 50kg / m3 ;

[0068] (3) Aging of blended fiber SiO2 alcohol gel felt: The alcohol gel felt prepared in step (2) was immersed in an alkaline ethanol solution for aging. The alkalinity in the ethanol was adjusted to pH 9 by trimethylamine alcohol solution. The aging temperature was 64°C and the aging time was 20 h.

[0069] (4) Preparation of blended fiber SiO2 aerogel felt: The alcohol gel felt aged in step (3) was subjected to supercritical CO2 drying to obtain a blended fiber SiO2 aerogel felt, wherein the drying process conditions are CO2 flow rate 500 L / h, drying temperature 55°C, drying pressure 15 MPa, and drying time 5 h;

[0070] (5) Preparation of multi-layer composite aerogel products: The blended fiber SiO2 aerogel felt prepared in step (4) was mixed with a 5 mm thick and 100 kg / m 3 The 70wt% alkali-free glass fiber + 30wt% PET fiber blended needle-punched felt is sewn with 120tex polyester twisted yarn to combine the upper and lower layers, and then a layer of 140μm POE / Al / PET aluminum foil composite film is hot-pressed on the outer surface of the sewn aerogel felt through a hot pressing process to finally produce a multi-layer composite structure aerogel product.

[0071] The volume density of the blended fiber SiO2 aerogel felt sample prepared above is 163kg / m 3 According to GB / T 10294-2008, the thermal conductivity is 0.0177W / (K·m) at 95℃, 0.0151W / (K·m) at 25℃, 0.0133W / (K·m) at -75℃, 0.0109W / (K·m) at -125℃ and 0.0079W / (K·m) at -175℃. The thermal conductivity at each temperature point is excellent.

[0072] The above multi-layer composite structure aerogel product has been tested and its natural thickness is 17mm and its volume density is 147kg / m 3 , the thermal conductivity at 25℃ is 0.0162W / (K·m), and the moisture permeability is 4.7*10 -10 g / (m 2 ·s·Pa). The product has good flexibility, good bending, compression and rebound performance, and after being soaked in liquid nitrogen for 72 hours, the material has no cracking or delamination.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A blended fiber SiO2 aerogel felt, characterized in that: The blended fiber SiO2 aerogel felt is in-situ composited with blended fiber needle felt and SiO2 aerogel, and has a thickness of 8 to 12 mm and a volume density of 130 to 180 kg / m 3 , thermal conductivity at 25°C ≤0.016W / (K·m), thermal conductivity at -75°C ≤0.0141W / (K·m), thermal conductivity at -125°C ≤0.012W / (K·m), thermal conductivity at -175°C ≤0.0092W / (K·m), volume water absorption ≤1%; wherein the blended fiber needle felt is a blend of 60% to 75% by mass of alkali-free glass fiber and 25% to 40% by mass of PET fiber; The method is as follows, comprising the following steps: (1) preparing a sol: mixing a silicon source, a solvent, and a catalyst in a mass ratio of 1:3-5.5:0.3-0.6, and stirring continuously at 55-60° C. for 5-6 hours to prepare a sol; the silicon source is prepared by mixing methyl orthosilicate and methyltrimethoxysilane or ethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:1-1.5; the solvent is methanol or ethanol, and the catalyst is a 0.1-0.3 mol / L dilute nitric acid aqueous solution; (2) preparing a blended fiber SiO2 alcohol gel felt: adding an organic base to the sol obtained in step (1) to adjust the pH to 7-9, then adding the blended fiber needle-punched felt to the obtained sol, impregnating and heating the gel to obtain an alcohol gel felt; the organic base is 0.4-0.8 mol / L tetramethylammonium hydroxide alcohol solution, tetraethylammonium hydroxide alcohol solution or trimethylamine alcohol solution; (3) aging the gel: placing the alcohol gel felt prepared in step (2) into an alcohol solution, and adding an alkaline solution to the alcohol solution to adjust the pH to 8-9, and aging at an aging temperature of 55° C. to 65° C. for 10 h to 24 h; the alcohol solution is a methanol or ethanol solution; the alkaline solution is a tetramethylammonium hydroxide alcohol solution, a tetraethylammonium hydroxide alcohol solution or a trimethylamine alcohol solution; (4) Drying the gel: The alcohol gel felt aged in step (3) is subjected to supercritical CO2 drying to obtain a blended fiber SiO2 aerogel felt.

2. The blended fiber SiO2 aerogel felt according to claim 1, characterized in that: The blended fiber needle felt has a thickness of 12 to 15 mm and a volume density of 40 to 60 kg / m 3 .

3. A multi-layer composite structure aerogel product, characterized in that: The fiber felt, the aerogel felt according to any one of claims 1 or 2 and the vapor barrier film are composited from bottom to top, and its natural thickness is 15±2mm and its volume density is 120-150kg / m 3 , thermal conductivity at 25℃ is 0.0158~0.164W / (K·m), and moisture permeability is 4.7*10 -10 ~8.7*10 -10 g / (m 2 ·s·Pa).

4. The multi-layer composite structure aerogel product according to claim 3, characterized in that: The vapor barrier film is an aluminum foil composite film, and the material structure is POE / Al / PET; the POE layer is 80-90 μm, the Al layer is 15-25 μm, the PET layer is 20-25 μm, and the total thickness of the composite film is 120-140 μm.

Citation Information

Patent Citations

  • Low-heat-conductivity-coefficient fiber composite aerogel wet felt and preparation method thereof

    CN115583829A

  • Flexible SiO2 aerogel felt for cold insulation

    CN115709590A